Statistical tools and packages for data collection, management, and analysis - A brief guide for health and biomedical researchers - Vishal Deo; Priya Ranganathan (Perspectives in Clinical Research)
Previous articles in this series have looked at various aspects of planning, designing, conducting and interpreting biomedical research. In this article, we offer an overview of some tools and resources available to health and biomedical researchers, to help them with their research.